Islam dan Pergumulan Budaya: Warisan Dahlan kepada Penerus Muhamadiyah - Saidun Derani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
This article explains the aculturation process between Islam and Indonesian traditional culture. The processcovers three procedures: ignoring Islamic teaching and accomodating the traditional values, combining Islamic teachingand old tradition like in pesantren community, and liberating people from old tradition by reform movement